Chemical Machining of Aluminum Alloy 2024: The Critical Roles of Temperature and Solution Concentration in Enhancing Corrosion Rate and Surface Texture - Muhammad, Ahmed K.; Mohammed, Tawfeeq W.; Resan, Kadhim K. (Journal of Engineering and Technological Sciences, 2024)
Chemical etching is a crucial process in materials science that involves controlling material removal through chemical reactions. It offers precise surface manipulation for various applications. In this study, the focus was on investigating the influence of temperature and etching solution concentration on the corrosion rate and surface roughness of aluminum alloy 2024. A range of temperatures (from 35 to 65°C) was selected with increments of 5 °C. Three concentrations (9, 20 and 29 Be) of the etching solution (ferric chloride) were examined. The experimental results revealed that both the corrosion rate and surface roughness increased with higher temperatures and concentrations. The values of corrosion rate and surface roughness varied from 1.15 x 10-4 mm/min and 1.208 μm, respectively at 35 °C, to 1.291x10-3 mm/min and 7.431 μm, respectively at 65 °C. However, the effect of temperature was found to be more significant than that of concentration for the range under study. Understanding the relationship between temperature, concentration, corrosion rate, and surface roughness in chemical etching of Al-2024 enables the optimization of the process for tailored material properties. This can be helpful in industrial application fields that require precise surface manipulation, such as automotive, airplanes, aerospace, medical, households and consumer electronics